Comparison of hepatic proliferative activity in chronic hepatitis B and C - S. SARIOĞLU; Ö. GÖNEN; A. KÜPELİOĞLU and İ. ŞİMŞEK and E. TANKURT and S. AKTAŞ and H. ABACIOĞLU and H. AKBAYLAR and A. KILIÇALP and Ö. SAĞOL and et al. (Turkish Journal of Gastroenterology, 2019)
-